Clinical value of YKL‐40 in patients with polymyositis/dermatomyositis: A cross‐sectional study and a systematic review. Issue 9 (15th July 2022) - Cui, Beibei; Chen, Yuehong; Luo, Fengming; Lin, Sang; Liu, Huan; Huang, Yupeng; Zhou, Yueyuan; Tian, Yunru; Yin, Geng; Xie, Qibing
Abstract: Introduction: We performed a cross‐sectional study to investigate the clinical usefulness of YKL‐40 in patients with dermatomyositis (DM) and conducted a systematic review to summarize the clinical value of YKL‐40 in patients with polymyositis (PM)/DM. Materials and methods: A cross‐sectional study and a systematic review were performed to study the clinical value of YKL‐40 in patients with PM/DM. Serum YKL‐40 level was detected using enzyme‐linked immunosorbent assay, and its association with clinical and laboratory parameters was analyzed. In the systematic review, electronic databases of OVID Embase, OVID Medline, and web of science were searched to collect studies that reported clinical use of YKL‐40 in patients with PM/DM. Results: In the cross‐sectional study, serum YKL‐40 level was higher in patients with DM than in healthy controls (median [interquartile range]: 84.09 [52.72–176.4] ng/ml versus 27.37 [12.30–53.58] ng/ml, p < 0.0001). Serum levels of YKL‐40 were associated with the course of DM (r = −0.469, p < 0.001), CRP (r = 0.303, p = 0.043), CK (r = 0.263, p = 0.037), and global disease activity (r = 0.628, p < 0.001). The area under the ROC curve was 0.835 (95% confidence interval 0.751–0.920). In the systematic review, a total of four studies were included with moderate to high quality. Serum level of YKL‐40 has the possibility for diagnosing PM/DM, identifying PM/DM patients with interstitial lung disease (ILD) or rapid progress ILD, and predicting death. Conclusion: Serum YKL‐40 level is a possible useful biomarker for PM/DM diagnosis and may be used to predict prognosis. Abstract : Serum YKL‐40 level was higher in patients with DM than in healthy controls (median [interquartile range]: 84.09 [52.72–176.4] ng/mL vs 27.37 [12.30–53.58] ng/mL, p < 0.0001). Serum levels of YKL‐40 were associated with the course of DM (r = −0.469, p < 0.0001), CRP (r = 0.303, p = 0.043), CK (r = 0.263, p = 0.037), and global disease activity (r = 0.628, p < 0.001). The area under the ROC curve was 0.835 (95% confidence interval 0.751–0.920).